Initiating the establishment of commercial stand at Tasik Besar Serkap, Riau, Indonesia: An early growth assessment of two peat swamp tree species - HENTI HENDALASTUTI RACHMAT; ATOK SUBIAKTO (Society for Indonesian Biodiversity, 2019)
Rachmat HH, Subiakto A. 2019. Initiating the establishment of commercial stand at Tasik Besar Serkap, Riau, Indonesia: An early growth assessment of two peat swamp tree species. Biodiversitas 20: 267-272. Degraded and converted peat swamp forest has enhanced the emission of CO2 and become one major contributor of huge greenhouse gas emission. Management unit at site level of KPH Tasik Besar Serkap covers a very wide area of more than 510.000 ha, dominated by 90% of peat swamp forest (PSF) which is susceptible to several disturbance sources (fires, illegal logging, land encroachment, alien species invasion, etc) and experiencing more deteriorated condition if there is no significant action carried out in managing its resources. Thus, it is important to improve the productivity of this PSF by planting it with native commercial tree species in order to maintain its role both in production and conservation aspects. The main objective of this study was to determine suitable PSF native species to rehabilitate highly degraded PSF in KPHP Tasik Besar Serkap. Two native PSF tree species were used namely Balangeran (Shorea balangeran) and Bintangur (Callophylum soulatri). Seedlings were planted at 4 x 3 meter spacing distance, each species was planted in a 1-ha plot, and thus the planting trial total area was 2 ha with 834 individual trees/species/ha. The survival rates at 6 months and 12 months after planting were 81.77% (682 seedlings/ha) and 58.6% (488 seedlings/ha) respectively for Balangeran, and 12.64% (105 seedlings/ha) and 10.34% (86 seedlings/ha) for Bintangur. The average heights at 6 and 12 months after planting for Balangeran were 111.54 cm (±16.731) and 206.03 cm (± 30.905) respectively, while for Bintangur 60.00 cm (± 12.921) and 72.76 cm (± 11.326) respectively. We also observed physical damage on planted seedlings, namely the occurrence of shoot and twig boring (pest) and seedling mortality caused by herbicide contact when our field staff applied herbicide at the experimental plots to ease the planted seedlings from weeds and other competitors. Borer was only identified in the surviving Balangeran seedlings at 12 months after planting with the intensity of attack of 17% . We did not observe similar case occurring in planted Bintangur. Seedling mortality rates caused by herbicide contact for Balangeran and Bintangur were 3.8% and 3,2% respectively. From the study result, it was concluded that only Balangeran was recommended to be planted for increasing the productivity of PSF in the scheme of commercial stand.